Utilization of Styrofoam Waste as An Asphalt Modifier to Support The Development Of Environmentally Road Pavements - Ulwiyah Wahdah Mufassirin Liana; Muhammad Jefri Prahmadanegara; Fitriyati Agustina (Department of Civil Engineering, Politeknik Negeri Bandung, 2026)
The rising demand for road infrastructure as well as vehicle growth needs high-performance and eco-friendly pavement materials. However, plastic waste, especially non-biodegradable Styrofoam, still remains a major environmental challenge. Previous studies have examined styrofoam in plastic-modified asphalt, but limited research has addressed the optimum styrofoam content using a multi-parameter Marshall performance approach under local aggregate conditions and Bina Marga 2024 specifications. This study aims to evaluate the effect of styrofoam waste as an asphalt modifier on the Marshall characteristics of Asphalt Concrete–Wearing Course (AC-WC) mixtures and to determine the optimum styrofoam content. Laboratory tests were conducted with styrofoam variations of 5.8%, 6.0%, and 6.2% at an Optimum Asphalt Content of 5.81%. Styrofoam was cut into 1 × 1 cm pieces before being mixed into hot asphalt, with the mixing process carried out according to Bina Marga specifications. Marshall parameters were analyzed, including stability, flow, density, VIM, VMA, VFA, and Marshall Quotient. The results indicate that styrofoam modification improves mixture stiffness, stability, and resistance to deformation. The optimum performance was achieved at 6.0% styrofoam content. The utilization of styrofoam waste has the potential to reduce plastic pollution while enhancing pavement performance, contributing to sustainable infrastructure development aligned with SDG 9.